Valorization of an agroextractive residue—Carnauba straw—for the production of bioethanol by simultaneous saccharification and fermentation (SSF) - Santos, Everaldo Silvino dos (2018)
In this study, the use of carnauba straw residue to produce cellulosic ethanol by simultaneous saccharification and fermentation (SSF) with three industrial yeasts was investigated. Hydrothermal (HT), alkaline (AL), and acidealkaline (AA) pretreatments were carried out on the residues, and the efficiency of the enzymatic hydrolysis of these residues was evaluated. The SSF was performed using Saccharomyces cerevisiae UFLA CA11, Saccharomyces cerevisiae CAT-1, and Kluyveromyces marxianus ATCC-36907 at 35, 40, and 45 C. The AL pretreatment resulted in the best removal of lignin and hemicellulose. In addition, enzymatic hydrolysis of the dry residue treated with AL converted 64.43% of the lignocel-lulosic biomass to sugars. SSF of the AL-pretreated residue using Kluyveromyces marxianus ATCC-36907 cultivated at 45 C produced 7.53 g/L ethanol